Communication—Evaporation Driven Micro/Nanofluidic Pumping Device. Issue 5 (1st January 2018) - Wang, Chenxi; Wang, Te; Mawatari, Kazuma; Kitamori, Takehiko
Abstract : A compact portable nanofluidic pump that enables precise manipulation of ultra-small amount of liquid is highly desirable for the trend in miniaturization. Here we develop an integrated micro/nanofluidic pumping device utilizing nanopillar structures with diminishing intervals and locally controlled evaporation. A continuous and steady flow rate of 2.7 pL/s was achieved for more than 12 h without external mechanical power source. The liquid transports in the nanofluidic channels were controllable by adjusting the temperature of evaporation surface. The picoliter-scale flow rates meet the demands for performing nanofluidic immunoassays and other interdisciplinary applications.